The effects of swimming training on bone tissue in adolescence - Gomez-Bruton, A.; Gonzalez-Agüero, A.; Gomez-Cabello, A.; Matute-Llorente, A.; Casajus, A. J.; Vicente-Rodriguez, G. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The aim was to analyze bone mineral content (BMC) and density (BMD) in regular swimming trained adolescents and the interaction that weigh-bearing sports may have on these values. Bone mass was evaluated by dual energy x-ray absorptiometry (DXA) and quantitative ultrasound (QUS) in 77 swimmers (34 females/43 males) and 52 normoactive controls (CG; 23 females/29 males) from 11 to 18 years. Swimmers who had performed or were performing other sports (OSP; 11 females/20 males) were compared with pure swimmers (PSW; 23 females/23 males). Both groups were compared with CG. Bone values were compared using analyses of covariance adjusting for height, calcium intake, subtotal lean (whole body lean minus head), and pubertal status. Male PSW showed lower BMD and BMC at several sites than male CG. However, for male OSP, only lumbar spine BMC was lower in OSP than male CG. Male PSW showed lower BMD and BMC when compared with male OSP. Female PSW showed higher arm BMD and lower leg BMC than female CG, while female OSP only presented lower leg BMC than female CG. Contrary to males, female-PSW presented higher BMD and BMC than female OSP. No differences in QUS values were found between swimmers and CG. To summarize, although more information is needed for females, it seems that for males, swimming is associated with lower BMC and BMD.